PANDANGAN MUI TENTANG NIKAH MUT'AH: ANALISIS PERSPEKTIF M. QURAISH SHIHAB - Arfiana, Shinta Nurul; Rouf, Abd. (MUSLIM HERITAGE, 2024)
AbstractM. Quraish Shihab, a renowned scholar, in his book "Perempuan," states that nikah mut'ah can be accepted in emergency and urgent situations with certain limitations and conditions, such as it must be conducted with honorable women. This statement has sparked controversy, prompting an examination of the views of the Indonesian Ulema Council (MUI) leaders in Malang City regarding the boundaries of nikah mut'ah from M. Quraish Shihab's perspective. This study aims to understand the permissible boundaries of nikah mut'ah according to M. Quraish Shihab and the perspectives of MUI leaders in Malang City regarding his fatwa on the permissibility of nikah mut'ah. This research is an empirical juridical study with a qualitative descriptive approach, gathering data through interviews and documentation from primary and secondary sources. The data processing involves editing, classification, verification, analysis, and conclusion drawing. The results indicate that the MUI leaders interviewed do not agree with the permissibility of nikah mut'ah based on "emergency or urgent" as its boundaries. They argue that the emergency concept proposed by M. Quraish Shihab does not apply in this context and emphasize the existence of alternative ways to prevent adultery. Additionally, they highlight the negative impacts of nikah mut'ah, especially on women, including the lack of legal protection and the risk of transmitting dangerous diseases such as HIV. The study concludes that although M. Quraish Shihab outlines certain limitations for the permissibility of nikah mut'ah, the MUI leaders in Malang City tend to reject this practice in all situations.AbstrakM. Quraish Shihab, seorang ulama terkenal, dalam bukunya “Perempuan,” menyatakan bahwa nikah mut’ah dapat diterima dalam situasi darurat dan mendesak dengan batasan dan syarat tertentu, seperti harus dilakukan dengan wanita yang terhormat. Pernyataan ini menimbulkan kontroversi, sehingga menarik untuk mengkaji pandangan Tokoh Majelis Ulama Indonesia (MUI) Kota Malang mengenai batasan nikah mut’ah dalam perspektif M. Quraish Shihab. Penelitian ini bertujuan untuk memahami batas-batas kebolehan nikah mut’ah menurut M. Quraish Shihab dan pandangan Tokoh MUI Kota Malang terhadap fatwa tersebut. Penelitian ini merupakan studi yuridis empiris dengan pendekatan deskriptif kualitatif, mengumpulkan data melalui wawancara dan dokumentasi dari sumber data primer dan sekunder. Proses pengolahan data meliputi teknik edit, klasifikasi, verifikasi, analisis, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa para tokoh MUI yang diwawancarai tidak sepakat dengan pembolehan nikah mut’ah berdasarkan “darurat atau mendesak” sebagai batasannya. Mereka berpendapat bahwa konsep darurat yang dikemukakan oleh M. Quraish Shihab tidak berlaku dalam konteks ini dan menekankan adanya alternatif lain untuk mencegah perbuatan zina. Selain itu, mereka menyoroti dampak negatif dari nikah mut’ah, terutama terhadap kaum wanita, termasuk kurangnya perlindungan hukum dan risiko penularan penyakit berbahaya seperti HIV. Kesimpulan penelitian ini menunjukkan bahwa meskipun M. Quraish Shihab mengemukakan batasan-batasan tertentu untuk kebolehan nikah mut’ah, pandangan tokoh MUI Kota Malang cenderung menolak praktik ini dalam segala situasi.